Enhanced Bioactivity of Pomegranate Peel Extract following Controlled Release from CaCO3 Nanocrystals. (12th February 2022) - Baldassarre, Francesca; Vergaro, Viviana; De Castro, Federica; Biondo, Francesca; Suranna, Gian Paolo; Papadia, Paride; Fanizzi, Francesco P.; Rongai, Domenico; Ciccarella, Giuseppe
Abstract : Pomegranate peel extract is rich of interesting bioactive chemicals, principally phenolic compounds, which have shown antimicrobial, anticancer, and antioxidative properties. The aim of this work was to improve extract' bioactivity through the adsorption on calcium carbonate nanocrystals. Nanocrystals revealed as efficient tools for extract adsorption reaching 50% of loading efficiency. Controlled release of the contained metabolites under acidic pH has been found, as it was confirmed by quantitative assay and qualitative study through NMR analysis. Specific functionality of inorganic nanocarriers could be also tuned by biopolymeric coating. The resulting coated nanoformulations showed a great antimicrobial activity against B. cinerea fungus preventing strawberries disease better than a commercial fungicide. Furthermore, nanoformulations demonstrated a good antiproliferative activity in neuroblastoma and breast cancer cells carrying out a higher cytotoxic effect respect to free extract, confirming a crucial role of nanocarriers. Finally, pomegranate peel extract showed a very high radical scavenging ability, equal to ascorbic acid. Antioxidant activity, measured also in intracellular environment, highlighted a protective action of extract-adsorbed nanocrystals twice than free extract, providing a possible application for new nutraceutical formulations.